Magnesium hydride film and preparation method and application thereof

By using a combination of ultrasonic cleaning and vacuum drying in the preparation of magnesium hydride films, the equipment requirements are simplified and the cost is reduced, and the problems of high equipment and long preparation time in the prior art are solved, so as to achieve efficient and safe magnesium hydride films are achieved. Preparation and application.

CN119284839APending Publication Date: 2025-01-10JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411426367.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing magnesium hydride film preparation equipment has high requirements, high cost, and long preparation time, making it difficult to meet the needs of rapid response and safety and efficiency.

Method used

The substrate was coated with dibutylmagnesium heptane solution after ultrasonic cleaning, and then heated in 6-9MPa hydrogen at 200-350°C to absorb hydrogen to prepare MgH2 films, simplifying equipment requirements and reducing costs.

Benefits of technology

It improves the preparation efficiency and response speed of MgH2 film, reduces the complexity of equipment and operation, is suitable for large-scale production and application, and is safe and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284839A_ABST
    Figure CN119284839A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium hydride film and a preparation method and application thereof, and the preparation method comprises the following steps: step 1, coating a heptane solution of dibutyl magnesium on a substrate after ultrasonic cleaning, and regulating and controlling the thickness of the MgH2 film; 2, vacuum drying is carried out, and dibutyl magnesium loaded on the substrate is obtained; and 3, hydrogen with the pressure of 6-9 MPa is introduced into the product obtained in the step 2, the temperature is increased to 200-350 DEG C for hydrogen absorption, and the MgH2 thin film coated on the substrate is obtained. In the first step, the substrate is a silicon wafer, glass or aluminum foil. The substrate is subjected to ultrasonic cleaning in an ethanol solution, and the mass fraction of the ethanol solution is 20-80%; and the concentration of the heptane solution of dibutyl magnesium is 0.1-5.0 M / L. The coating frequency is 2-3 times. The thickness of the MgH2 film is regulated and controlled by changing the concentration of the dibutyl magnesium solution and increasing and decreasing the coating times. According to the method, the requirement for equipment for preparing the MgH2 thin film can be lowered, and the preparation efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a film and a preparation method and application thereof, and in particular to a magnesium hydride film and a preparation method and application thereof. Background Art

[0002] Since hydrogen molecules are small and light, once they leak and encounter open flames, they may explode, causing unpredictable damage to laboratories and personal safety. Therefore, gas-induced color sensors are a critical link in hydrogen applications and play a role in detecting whether hydrogen has leaked. Magnesium hydride film is a colorless and transparent form. Nanostructured magnesium film absorbs hydrogen at a certain temperature and hydrogen pressure, and changes from a metallic state to a transparent semiconductor state. In the field of hydrogen sensors, the hydrogen-induced color change property of magnesium hydride film is used to detect whether hydrogen has leaked and prevent dangerous accidents. The visible light transmittance of the Mg-Zr-Ni ternary system film prepared by Tajima et al. after hydrogenation can be increased from 5.2% to 44.7%, and the reflectivity can be reduced from 53.45% to 7.42%. The reaction process only takes 10s. Slaman et al. used Mg-Ti alloy film as a dimming layer to make an optical fiber sensor. When the hydrogen concentration in the surrounding environment changes from 0% to 1%, the reflectivity of the optical fiber film can drop from 61% to 7% within 8 to 20 seconds. The higher the oxygen concentration in the atmosphere, the longer the reaction time. In response to the sensor's demand for response speed, Zhao et al. prepared amorphous and crystalline Pd / Mg and Pd / Mg-Ni films respectively. The study found that the amorphous film has faster optical conversion characteristics than the corresponding crystalline film. The amorphous magnesium-based structure can prevent the formation of a barrier hydride layer and promote the diffusion of hydrogen atoms in the magnesium-based layer. Based on this discovery, the response characteristics of hydrogen-induced chromic magnesium-based films can be improved by amorphization.

[0003] MgH2 film can be switched between the dehydrogenation state and the hydrogen absorption state, realizing the transition from non-transparent state to transparent state. Based on this principle, it is used to detect whether hydrogen has leaked. There are two methods for preparing thin films: magnetron sputtering and chemical vapor deposition. The magnetron sputtering method is to use a magnetron sputtering instrument to sputter the modulated target material onto the substrate through high-speed rotation. Although this type of method can prepare MgH2 film, it has high requirements for instruments and equipment, and the experimental parameters are difficult to grasp. It has high requirements for the instrument operation technology of the experimenter, and the cost of manufacturing thin films is high. The chemical vapor deposition method deposits a film on the substrate by activating the reactants. The CVD method has higher uniformity and has the advantages of being more economical, having a high deposition rate, and being able to obtain a post-coating compared to the magnetron sputtering method. However, the CVD method needs to be carried out under high temperature conditions, has high requirements for the substrate, and the required chemical precursors are generally highly toxic and dangerous, and the price is also relatively expensive. MgH2 is prepared using magnesium powder and hydrogen, which takes 3 to 4 days and requires five hours of ball milling. Usable MgH2 can only be obtained at 653K and a hydrogen pressure of about 7MPa. Summary of the invention

[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a magnesium hydride film. Another purpose of the present invention is to provide a magnesium hydride film. A further purpose of the present invention is to provide an application of a magnesium hydride film in an optical fiber hydrogen sensor.

[0005] Technical solution: A method for preparing a magnesium hydride film according to the present invention comprises the following steps:

[0006] Step 1, coating a heptane solution of dibutyl magnesium on the substrate after ultrasonic cleaning to adjust the thickness of the MgH2 film;

[0007] Step 2, vacuum drying to obtain dibutyl magnesium supported on a substrate;

[0008] Step 3: introduce 6-9 MPa hydrogen into the product obtained in step 2, raise the temperature to 200-350° C. to absorb hydrogen, and obtain a MgH2 film coated on the substrate.

[0009] Furthermore, in step 1, the substrate is a silicon wafer, glass or aluminum foil. The substrate is ultrasonically cleaned in an ethanol solution, and the mass fraction of the ethanol solution is 20 to 80%. The concentration of the heptane solution of dibutyl magnesium is 0.1 to 5.0 M. The number of coatings is 1 to 10 times. The thickness of the MgH2 film is regulated by changing the concentration of the dibutyl magnesium solution and increasing or decreasing the number of coatings.

[0010] Furthermore, in step 2, the vacuum drying temperature is 0 to 50° C., and the time is 6 to 48 hours.

[0011] Furthermore, in step three, the hydrogen absorption time is 12 to 48 hours.

[0012] The magnesium hydride film is obtained by the above-mentioned method for preparing the magnesium hydride film.

[0013] Application of the above magnesium hydride film in optical fiber hydrogen sensor.

[0014] Preparation principle: After dibutyl magnesium is crystallized, it can grow into a film on a substrate in an anhydrous and oxygen-free environment with appropriate hydrogen and temperature.

[0015] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0016] 1. It can reduce the equipment requirements for preparing MgH2 thin films, improve the preparation efficiency of MgH2 thin films, and obtain the optimal process for MgH2 printing film formation;

[0017] 2. The thickness of the MgH2 film can be adjusted by diluting the dibutyl magnesium solution (thinning) and increasing the number of coatings (thickening) on ​​the substrate to obtain MgH2 films of different thicknesses;

[0018] 3. Compared with the preparation of MgH2 using magnesium powder and hydrogen, the preparation time is shorter and the steps are simpler;

[0019] 4. The operation is simple, safe and efficient, the required equipment is simple, the experimental instruments required in the film preparation process are simple, the preparation cost is low, and it is suitable for promotion and mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the XRD pattern of the MgH2 film of Example 1 of the present invention;

[0021] Figure 2 is a SEM image of the MgH2 film obtained in Example 1 of the present invention;

[0022] Figure 3 is a SEM image of the MgH2 film obtained in Example 2 of the present invention;

[0023] Figure 4 is a SEM image of the MgH2 film obtained in Example 3 of the present invention;

[0024] Figure 5 is a SEM image of the MgH2 film obtained in Example 4 of the present invention;

[0025] Figure 6 This is a constant temperature hydrogen release diagram of MgH2 at 340°C in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0027] Example 1

[0028] A method for preparing a magnesium hydride film comprises the following steps:

[0029] (1) A 10 mm × 10 mm glass substrate was selected and ultrasonically cleaned in an ethanol solution with a mass fraction of 80 wt %, and then dried for later use.

[0030] (2) A heptane solution of dibutyl magnesium with a concentration of 1 M / L is coated on the substrate twice.

[0031] (3) Dry under vacuum at 15° C. for 6 hours in a water-free and oxygen-free Mikaelona glove box to remove the heptane solution.

[0032] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 8 MPa of hydrogen is introduced, the temperature is raised to 320° C., and the hydrogen absorption time is maintained for 20 hours to obtain a MgH2 film coated on the substrate.

[0033] like Figure 1 The appearance of MgO in the XRD of the MgH2 film obtained in Example 1 is due to the fact that the magnesium hydride film is thin and easily oxidized. It is recommended to place it in a closed, water-free and oxygen-free atmosphere. Figure 2 , the thickness of the MgH2 film is 1.46μm, and the film thickness is in the micron level.

[0034] Example 2

[0035] A method for preparing a magnesium hydride film comprises the following steps:

[0036] (1) A 10 mm × 10 mm glass substrate was selected and ultrasonically cleaned in an ethanol solution with a mass fraction of 80 wt %, and then dried for later use.

[0037] (2) A heptane solution of dibutyl magnesium with a concentration of 1 M / L was coated on the substrate three times.

[0038] (3) Dry under vacuum at 15° C. for 6 hours in a water-free and oxygen-free Mikaelona glove box to remove the heptane solution.

[0039] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 8 MPa of hydrogen is introduced, the temperature is raised to 320° C., and the hydrogen absorption time is maintained for 20 hours to obtain a MgH2 film coated on the substrate.

[0040] like Figure 3 The magnesium hydride film obtained in Example 2 has good crystallinity, and the thickness of the MgH2 film can be increased by increasing the number of coatings. The SEM image shows that the film thickness increases to 12.1 microns.

[0041] Example 3

[0042] A method for preparing a magnesium hydride film comprises the following steps:

[0043] (1) A 10 mm × 10 mm glass substrate was selected and ultrasonically cleaned in an ethanol solution with a mass fraction of 80 wt %, and then dried for later use.

[0044] (2) A heptane solution of dibutyl magnesium with a concentration of 1 M / L is coated on the substrate twice.

[0045] (3) Dry under vacuum at 15° C. for 6 hours in a water-free and oxygen-free Mikaelona glove box to remove the heptane solution.

[0046] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 6 MPa of hydrogen is introduced, the temperature is raised to 320° C., and the hydrogen absorption time is maintained for 20 hours to obtain a MgH2 film coated on the substrate.

[0047] like Figure 4 The magnesium hydride thin film obtained in Example 3 has uniform crystal distribution, and the film surface roughness is large, and the specific surface area is large, which provides more sites for the adsorption of hydrogen.

[0048] Example 4

[0049] A method for preparing a magnesium hydride film comprises the following steps:

[0050] (1) A 10 mm × 10 mm glass substrate was selected and ultrasonically cleaned in an ethanol solution with a mass fraction of 80 wt %, and then dried for later use.

[0051] (2) A heptane solution of dibutyl magnesium with a concentration of 1 M / L is coated on the substrate twice.

[0052] (3) Dry under vacuum at 15° C. for 6 hours in a water-free and oxygen-free Mikaelona glove box to remove the heptane solution.

[0053] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 8 MPa of hydrogen is introduced, the temperature is raised to 250° C., and the hydrogen absorption time is maintained for 20 hours to obtain a MgH2 film coated on the substrate.

[0054] like Figure 5 The magnesium hydride thin film obtained in Example 4 has uniform crystal distribution, and the film surface roughness is large, and the specific surface area is large, which provides more sites for the adsorption of hydrogen.

[0055] Example 5

[0056] A method for preparing a magnesium hydride film comprises the following steps:

[0057] (1) A 10 mm×10 mm silicon wafer was selected as a substrate, and after ultrasonic cleaning in an ethanol solution with a mass fraction of 20 wt%, it was dried for later use.

[0058] (2) A heptane solution of dibutyl magnesium with a concentration of 0.1 M / L is coated on the substrate once.

[0059] (3) Drying under vacuum at 0° C. for 48 hours in a water-free and oxygen-free Mikaelona glove box to remove the heptane solution.

[0060] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 9 MPa of hydrogen is introduced, the temperature is raised to 200° C., and the hydrogen absorption time is maintained for 48 hours to obtain a MgH2 film coated on the substrate.

[0061] Example 6

[0062] A method for preparing a magnesium hydride film comprises the following steps:

[0063] (1) Aluminum foil was selected as a substrate, and after ultrasonic cleaning in an ethanol solution with a mass fraction of 80 wt%, it was dried for later use.

[0064] (2) A heptane solution of dibutyl magnesium with a concentration of 5.0 M / L was coated on the substrate 10 times.

[0065] (3) The mixture was dried under vacuum at 50° C. for 27 hours in a water-free and oxygen-free environment in a Mikaelona glove box to remove the heptane solution.

[0066] (4) The dibutyl magnesium coated on the substrate obtained in the above step (3) is placed in a reactor, 7 MPa of hydrogen is introduced, the temperature is raised to 350° C., and the hydrogen absorption time is maintained for 12 hours to obtain a MgH2 film coated on the substrate.

[0067] Example 7

[0068] This example aims to explore the relationship between the thickness of the MgH2 film and the number of coatings and the concentration of the dibutyl magnesium solution.

[0069] This example designs an orthogonal factor test, and the remaining steps are the same as those in Example 1, except that the variables are as follows: (1) the concentrations of the dibutyl magnesium solution are 1.0 M / L, 2.0 M / L, 3.0 M / L, and 4.0 M / L. (2) the number of coatings is 2, 3, and 4. The thickness of the MgH2 film obtained by the test is listed in Table 1 below.

[0070] Table 1 Relationship between coating times and MgH2 film thickness control

[0071]

[0072] Application Examples

[0073] The magnesium hydride films obtained in Examples 1 to 6 were respectively applied in optical fiber hydrogen sensors. The specific steps are: in an atmosphere without water and oxygen, the magnesium hydride film was placed in the sensor to form a complete part. The hydrogen release performance test was carried out, and it was found that the film sensor prepared by Example 1 gradually changed from a transparent state to a non-transparent state in 60 minutes, and the MgH2 film was unevenly distributed. It can be seen that Example 1 is the best example.

[0074] Comparative Example 1

[0075] The remaining steps of this comparative example are the same as those of Example 1, except that the heptane solution of dibutyl magnesium is replaced with magnesium powder. The obtained magnesium hydride film is made into an optical fiber hydrogen sensor according to the method of the application example. Its hydrogen release performance at 200°C and within 60 minutes is tested. The results show that the film sensor prepared by Comparative Example 1 does not show the film transition to a non-transparent state within 60 minutes. Compared with Example 1, the MgH2 film is unevenly distributed.

[0076] Comparative Example 2

[0077] The remaining steps of this comparative example are the same as those of Example 1, except that the concentration of the heptane solution of dibutyl magnesium is replaced with 0.01 M / L. The obtained magnesium hydride film is made into an optical fiber hydrogen sensor according to the method of the application example. Its hydrogen release performance at 200°C within 60 minutes is tested. The results show that the film sensor prepared by Comparative Example 2 does not show a transition from a non-transparent state within 60 minutes. Compared with Example 1, the MgH2 film is unevenly distributed.

[0078] Comparative Example 3

[0079] The remaining steps of this comparative example are the same as those of Example 1, except that the concentration of the heptane solution of dibutyl magnesium is replaced with 6M / L. The obtained magnesium hydride film is made into an optical fiber hydrogen sensor according to the method of the application example. The hydrogen release performance thereof is tested at 200°C for 60 minutes. The results show that the film sensor prepared by Comparative Example 3 does not show a transition from a non-transparent state within 60 minutes. Compared with Example 1, the MgH2 film is unevenly distributed.

[0080] Comparative Example 4

[0081] The remaining steps of this comparative example are the same as those of Example 1, except that step 3 is replaced by introducing 4MPa hydrogen into the product of step 2, and the temperature is raised to 180°C for hydrogen absorption. The obtained magnesium hydride film is made into an optical fiber hydrogen sensor according to the preparation method of the application example. Its hydrogen release performance at 200°C and within 60 minutes is tested. The results show that the film sensor prepared by comparative example 4 is always in a non-transparent state within 60 minutes. Compared with Example 1, no MgH2 peak is found in XRD.

[0082] Comparative Example 5

[0083] The remaining steps of this comparative example are the same as those of Example 1, except that step 3 is replaced by introducing 10MPa hydrogen into the product of step 2, and the temperature is raised to 360°C for hydrogen absorption. The obtained magnesium hydride film is made into an optical fiber hydrogen sensor according to the preparation method of the application example. The dehydrogenation performance at 200°C and within 60 minutes is tested. The results show that the transparent state of the thin film sensor prepared by comparative example 5 gradually disappears within 60 minutes, but compared with Example 1, the distribution of the MgH2 film is uneven.

Claims

1. A method for preparing a magnesium hydride thin film, characterized in that: The following steps are involved: Step 1, coating a heptane solution of dibutyl magnesium on the substrate after ultrasonic cleaning to adjust the thickness of the MgH2 film; Step 2, vacuum drying to obtain dibutyl magnesium supported on a substrate; Step 3: introduce 6-9 MPa hydrogen into the product obtained in step 2, raise the temperature to 200-350° C. to absorb hydrogen, and obtain a MgH2 film coated on the substrate.

2. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 1, the substrate is a silicon wafer, glass or aluminum foil.

3. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 1, the substrate is ultrasonically cleaned in an ethanol solution, and the mass fraction of the ethanol solution is 20-80%.

4. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 1, the concentration of the heptane solution of dibutyl magnesium is 0.1-5.0 M / L.

5. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 1, the coating is applied 1 to 10 times.

6. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 1, the thickness of the MgH2 film is controlled by changing the concentration of the dibutyl magnesium solution and increasing or decreasing the number of coating times.

7. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 2, the vacuum drying temperature is 0 to 50° C. and the time is 6 to 48 hours.

8. The method for preparing a magnesium hydride thin film according to claim 1, characterized in that: In the step 3, the hydrogen absorption time is 12 to 48 hours.

9. A magnesium hydride thin film obtained according to the method for preparing a magnesium hydride thin film according to any one of claims 1 to 8.

10. Use of the magnesium hydride film according to claim 9 in an optical fiber hydrogen sensor.